Historyczno-filozoficzne aspekty polemologiczne a implikacje wychowawczo-kulturowe = Historical and philospophical polemological aspects and educational and cultural implications - Małachowski, Ryszard (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article concerns the interdisciplinary recognized aspects of war and struggle (polemological factors) which took place in the ancient and contemporary, historically conditioned, European civilization and cultural space. It shows mutual implications of totalitarianism explained by the following contents: philosophical, related to political science, political, moral-ethical, religious, artistic, cosmological, economic and anthropological. These contents are educational by the nature of its impact on individuals, people, communities and creative nations as well as the ones that contribute to the formation of human history.
Keywords: filozofia wychowania; filozofia chrześcijańska; totalitaryzm